2021
DOI: 10.1039/d0qm00885k
|View full text |Cite
|
Sign up to set email alerts
|

New multifunctional benzophenone-based photoinitiators with high migration stability and their applications in 3D printing

Abstract: A series of photoinitiators based on benzophenone scaffold are developed for LED photopolymerization. Excellent photoinitiation abilities are obtained and 3D printing experiments are carried out successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…these compounds could initiate the polymerization alone. We also reported that the 3-component (BT/Iod/Amine) PI system has higher conversion efficacy than that of 2-component (such as BT/Iod) [23]. This article will present, for the first time, the kinetics and the general conversion features of the 3-component (BT/Iod/Amine) PI system based on the proposed mechanism of Liu et al [22] for both FRP and CP.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…these compounds could initiate the polymerization alone. We also reported that the 3-component (BT/Iod/Amine) PI system has higher conversion efficacy than that of 2-component (such as BT/Iod) [23]. This article will present, for the first time, the kinetics and the general conversion features of the 3-component (BT/Iod/Amine) PI system based on the proposed mechanism of Liu et al [22] for both FRP and CP.…”
Section: Introductionmentioning
confidence: 83%
“…Monomer M couples with radicals R and S (for FRP), and with couples with radical R' (for CP). A specific measured system of related to Figure 1 was reported by Liu et al [23], in which their Scheme 4 proposed a 3-component system of BT/Iod/EDB, where BT is benzophenonetriphenylamine photoinitiator, with Iod being the iodonium salt (oxidizing agent), and the amine EDB is ethyl 4-(dimethylamino)benzoate. Monomer rimethylolpropane triacrylate (TMPTA), and (3,4-epoxycyclohexane)methyl 3,4-epoxycyc-lohexylcarboxylate (EPOX) are teh functional groups for FRP and CP, respectively, via radicals of Ar* and EDB(-H)* (for FRP), and BT *+ (for CP).…”
Section: Photochemical Kineticsmentioning
confidence: 92%
See 3 more Smart Citations